PERAN ISTRI DALAM PEMBENTUKAN KELUARGA SAKINAH MENURUT AL-QUR’AN (PERSPEKTIF TAFSIR AL-MISBAH DAN TAFSIR AL-AZHAR) - Mardiyana, Alfa (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2017)
The family is the small society but has a very large role in a nation. In the family has a woman (wife) is very many the role of the family in the make of a family, comfortable, peaceful and harmonis or can we call the happy family. This priority of the attitude and the nature of the woman (wife), because of the woman is what will be the nation's character will be grow. Existence, responsibility (liability), as well as their rights also must be known to determine how the role of women in the establishment of harmonis family. This resesarch is useful for writers to add insight  the mindset, attitudes, and experiences in an effort to improve the quality of learning, by understanding the nature of wife role in the establishment of harmonious family. The etica of wife in the establishment of harmonious family perspective according to the Qur'an perspective Tafsir Al-Misba>h and Tafsir Al-Azhar explained that a role to make  by wife in terms of family formation sakinah, such as  those reviewed in the perspective of Tafsir Al-Misba>h and Tafsir Al-Azhar. From these results, the authors concluded that the perspective of perspective Tafsir Al-Misba>h and Tafsir Al-Azhar about the etica of wife in happy family according to the Qur'an are the characters in a woman who reflects the character that excels in a family in accordance with the teachings of the Quran. Superior female characters, which have the life processing, habituation, exemplary, find out the obligations and rights within the family. A wife should know the importance of the role of the family, and  there is phrase  al- mar'ah , al-'Imad al-bilad {female pillar of the state), the essence is not missed when it is said that al-usrah ?imad al- bilad biha tah}ya wa biha} tamu>t (family is the pillar of the state, with the families that state to rise or fall). Key words: Role of Wife, Family Sakinah, Perspectives Tafsir Al-Misba>h and Tafsir Al-Azhar.